Pengaruh Booklet Kesiapsiagaan menghadapi Bencana terhadap Peningkatan Perilaku Ibu Balita - Renidayati Renidayati; Annisa Alzura Fatihah; Tasman Tasman; Elvia Metti; Zolla Amely Ilda (Jurnal Sehat Mandiri, 2024)
Padang City ranks 4th out of 19 districts/cities with a high risk class for disasters, especiallyearthquakes and tsunamis. In disaster situations, children are often the largest group of victimsdue to their inability to protect themselves and are out of reach of their parents, so the role of mothers of toddlers is very important in protecting toddlers. This study aims to determine the effect of booklets on the behavior of mothers of toddlers about disaster preparedness in Pasia Nan Tigo Village, Padang. Research design using Quasi-experimental with One Group Pretest and Posttest Design. Research time in September 2023- July 2024. The population was all mothers who brought their children to the posyandu in Pasia Nan Tigo village with a sample of 57 mothers of toddlers taken with Cluster Sampling technique. Data collection using a questionnaire. Data analysis using T-dependent test and Wilcoxon test. The average knowledge before and after being given a disaster preparedness booklet increased from 12.91 to 14.40. The average attitude also increased from 47.07 to 50.04. Similarly, the average action increased from 6.98 to 8.74. There is an effect of knowledge, attitudes, and actions before and after being given a disaster preparedness booklet for mothers of toddlers with a p-value = 0.000